A high-quality gallium-containing nanocrystal emitting pure blue light and a method for preparing the same
Patent Information
- Application Number
- CN202610790813.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-03
- Publication Date
- 2026-08-18
AI Technical Summary
从理论上看,纯ZnSe量子点有望实现色坐标良好的蓝光发射,但在实际合成过程中往往面临发光效率低、表面缺陷多及光稳定性不足等问题
[0015] Therefore, this invention employs the aforementioned high-quality gallium-containing nanocrystals that emit pure blue light and their preparation method. By introducing Ga doping into ZnSe quantum dots, ZnSe:Ga quantum dots are prepared, achieving pure blue light emission from the ZnSe system, with the emission peak position adjustable to between 450-460 nm. Furthermore, by epitaxially growing a shell layer, surface defects and interfacial nonradiative recombination are effectively suppressed, significantly improving the stability and optical performance of the quantum dots. The constructed ZnSe:Ga/ZnSeS/ZnS core-shell structure quantum dots exhibit high luminous efficiency. Combined with additional ligands to further passivate surface defects, their quantum yield can reach over 85%, laying a solid foundation for realizing high-performance blue QLED emitting layer materials.
Smart Images

Figure CN122587708A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of semiconductor materials technology, and in particular to a high-quality gallium-containing nanocrystal that emits pure blue light and its preparation method. Background Technology
[0002] Red and green QLEDs, as representatives of the next generation of light-emitting display technologies, have demonstrated excellent luminous performance and device stability. However, compared with red and green QLEDs, blue QLEDs still lag significantly behind in terms of external quantum efficiency and lifetime, which severely restricts the practical application of full-color displays and related devices. The fundamental reason is that blue quantum dots typically have a wider bandgap, making it easier to introduce multiple exciton nonradiative quenching channels; at the same time, achieving short-wavelength emission often requires a stronger quantum confinement effect, resulting in a significant blue shift in the emission spectrum, making it difficult for some systems to obtain stable and high-purity deep blue emission.
[0003] Therefore, finding a novel quantum dot luminescent material with excellent optical properties, low cost, environmental friendliness, and the ability to emit pure blue light is of great significance. ZnSe quantum dots do not contain typical heavy metals, have low toxicity, and are relatively inexpensive to produce, making them more environmentally friendly. Theoretically, pure ZnSe quantum dots hold promise for achieving blue light emission with good color coordinates, but in practical synthesis, they often face problems such as low luminous efficiency, numerous surface defects, and insufficient photostability. Summary of the Invention
[0004] The purpose of this invention is to provide a high-quality gallium-containing nanocrystal that emits pure blue light and its preparation method. By introducing Ga doping into ZnSe quantum dots, ZnSe:Ga quantum dots are prepared, achieving pure blue light emission from the ZnSe system with an emission peak position adjustable between 450-460 nm. Furthermore, by epitaxially growing a shell layer, surface defects and interfacial nonradiative recombination are effectively suppressed, significantly improving the stability and optical performance of the quantum dots. The constructed ZnSe:Ga / ZnSeS / ZnS core-shell structure quantum dots exhibit high luminous efficiency. Combined with additional ligands to further passivate surface defects, their quantum yield can reach over 85%, laying a solid foundation for realizing high-performance blue QLED light-emitting layer materials.
[0005] To achieve the above objectives, the present invention provides a method for preparing high-quality gallium-containing nanocrystals that emit pure blue light, comprising the following steps: S1. Prepare zinc precursor solution, gallium precursor solution and group VI precursor solution, wherein the element in group VI precursor solution is one or both of selenium and sulfur; S2. Under a protective atmosphere, the organic amine solvent is heated, and a Group VI precursor solution is added, followed by a zinc precursor solution and a gallium precursor solution. The reaction generates gallium-doped nanocrystal nuclei. Then, the Group VI precursor solution, zinc precursor solution, and gallium precursor solution are added dropwise to obtain gallium-doped quantum dots. S3. After the reaction is complete, lower the temperature and inject hydrofluoric acid solution into the reaction system to clean the surface of the nanocrystal nuclei. S4. After cleaning, the reaction system is heated and a mixed solution of zinc precursor solution and group VI precursor solution is added to grow a transition shell layer epitaxially on the surface of the nanocrystal nucleus. Finally, a mixed solution of zinc precursor solution and organic alcohol is added to grow the outer shell layer. S5. After the outer shell layer growth is completed, the temperature is lowered to room temperature, and an antisolvent is added to precipitate high-quality gallium-containing nanocrystals that emit pure blue light.
[0006] Preferably, in S1, the zinc precursor solution is one or more of diethylzinc solution and zinc oleate solution; the zinc oleate solution is prepared by dissolving zinc acetate in a mixed solvent of oleylamine, oleic acid and octadecene, wherein the volume ratio of oleylamine, oleic acid and octadecene is 1:1:8 and the dissolution temperature is 80-120℃.
[0007] Preferably, in S1, the gallium precursor solution is prepared by dissolving gallium chloride in a mixed solvent of oleylamine and octadecene to obtain a gallium precursor solution. The concentration of the prepared gallium precursor solution is 0.1 mol / L, the volume ratio of oleylamine to octadecene is 1:9, and the dissolution temperature is 80-120℃.
[0008] Preferably, in S1, the preparation of the Group VI precursor solution is as follows: the elemental substance of Group VI is dissolved in tri-n-octylphosphine to obtain the Group VI precursor solution, and Group VI precursor solutions with concentrations of 1 mol / L and 0.1 mol / L are prepared respectively.
[0009] Preferably, in step S2, the organic amine solution is heated to 100-120°C, evacuated for 30-60 minutes, and then heated to 300°C. The organic amine is a chain-like primary amine, which is one of oleylamine or octadecylamine. The concentration of the Group VI precursor solution is 1 mol / L, and the dropping rate of the Group VI precursor solution, zinc precursor solution, and gallium precursor solution is 1-2 mL / h.
[0010] Preferably, in S3, the temperature is reduced to 110°C.
[0011] Preferably, in S4, when the temperature is raised to 300°C, the concentration of the Group VI precursor solution during the growth of the transition shell is 0.1 mol / L, the organic alcohol is a chain thiol, and the chain thiol is octylthiol.
[0012] Preferably, in S4, the nanocrystal nucleus is one of ZnSe, ZnS, or ZnSeS.
[0013] Preferably, in S5, the antisolvent is one or more of acetone, methanol, and ethanol.
[0014] The present invention also provides a high-quality gallium-containing nanocrystal that emits pure blue light, which is prepared by the method described above for preparing a high-quality gallium-containing nanocrystal that emits pure blue light.
[0015] Therefore, this invention employs the aforementioned high-quality gallium-containing nanocrystals that emit pure blue light and their preparation method. By introducing Ga doping into ZnSe quantum dots, ZnSe:Ga quantum dots are prepared, achieving pure blue light emission from the ZnSe system, with the emission peak position adjustable to between 450-460 nm. Furthermore, by epitaxially growing a shell layer, surface defects and interfacial nonradiative recombination are effectively suppressed, significantly improving the stability and optical performance of the quantum dots. The constructed ZnSe:Ga / ZnSeS / ZnS core-shell structure quantum dots exhibit high luminous efficiency. Combined with additional ligands to further passivate surface defects, their quantum yield can reach over 85%, laying a solid foundation for realizing high-performance blue QLED emitting layer materials.
[0016] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0017] Figure 1 These are the spectral and electron microscope images of high-quality gallium-containing nanocrystals emitting pure blue light and their preparation method according to the present invention, Examples 1-2 and Comparative Example 1, wherein (a) is the UV-Vis absorption spectroscopy test result of Examples 1-2 and Comparative Example 1, (b) is the fluorescence spectroscopy test result of Examples 1-2 and Comparative Example 1, (c) is the photoluminescence stepwise redshift spectroscopy test result of Example 2, and (d) is the transmission electron microscope image of ZnSe:Ga quantum dots prepared in Example 2; Figure 2 The XRD patterns of ZnSe:Ga / ZnSeS / ZnS core-shell structured quantum dots prepared in Examples 1-2 and Comparative Example 1 are XRD patterns of high-quality gallium-containing nanocrystals that emit pure blue light and their preparation method according to the present invention. Figure 3 This is a transmission electron microscope (TEM) image of a gallium-containing high-quality nanocrystal that emits pure blue light and its preparation method, as well as TEM images of samples prepared in Examples 1-2 and Comparative Example 1. (a) is a TEM image of the sample prepared in Comparative Example 1, (b) is a TEM image of the sample prepared in Example 1, and (c) is a TEM image of the sample prepared in Example 2. Figure 4This invention relates to a high-quality gallium-containing nanocrystal that emits pure blue light and its preparation method, as well as the relationship between the external quantum efficiency (EQE) of a QLED device and current density. Figure 5 This invention relates to a high-quality gallium-containing nanocrystal that emits pure blue light and its preparation method. The QLED device achieves an initial brightness of 5700 cd / m². 2 Results of working life test under the specified conditions. Detailed Implementation
[0018] The technical solution of the present invention will be further described below with reference to the accompanying drawings and embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention should be considered equivalent substitutions and are included within the protection scope of the present invention. Furthermore, it should be understood that after reading the contents of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims and are all within the protection scope of the present invention.
[0019] In this document, the term "embodiment" means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The term "embodiment" appearing in various places throughout the specification does not necessarily refer to the same embodiment, nor does it specifically limit its independence or connection with other embodiments. In principle, in this application, as long as there are no technical contradictions or conflicts, the technical features mentioned in each embodiment can be combined in any way to form corresponding implementable technical solutions.
[0020] Unless otherwise defined, the technical terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the use of related terms herein is merely for the purpose of describing particular embodiments and is not intended to limit this application.
[0021] In this invention, unless otherwise specified, all other test materials and instruments are conventional test materials in the field and can be purchased through commercial channels.
[0022] Example 1 This invention provides a high-quality gallium-containing nanocrystal that emits pure blue light, and its preparation method includes the following steps: S1. Preparation of zinc precursor solution, gallium precursor solution and Group VI precursor solution: Group VI precursor solution: Add 1.580g selenium powder and 20mL tri-n-octylphosphine to a reaction flask, heat and stir at 100℃ until the solid dissolves and becomes a pale yellow transparent solution, which is the selenium source solution with a concentration of 1mol / L. Add 0.158g of selenium powder and 20mL of tri-n-octylphosphine to a reaction flask, heat and stir at 100℃ until the solid dissolves and becomes a pale yellow transparent solution, thus obtaining the selenium source solution with a concentration of 0.1mol / L. Gallium precursor solution: 0.176 g gallium chloride was dissolved in 10 mL of a mixed solvent of oleylamine and octadecene to prepare a gallium precursor solution with a concentration of 0.1 mol / L, a volume ratio of oleylamine to octadecene of 1:9, and a dissolution temperature of 100 °C.
[0023] Zinc precursor solution: Zinc oleate solution was prepared by dissolving 0.1835 g of zinc acetate in 10 mL of a mixed solvent of oleylamine, oleic acid and octadecene at a dissolution temperature of 100 °C.
[0024] Diethylzinc solution: Dissolve commercially available diethylzinc in water to obtain a 1 mol / L diethylzinc solution.
[0025] Sulfur precursor solution: Add 0.064g of sulfur powder and 20mL of tri-n-octylphosphine to a reaction flask, heat and stir at 100℃ until the solid dissolves and becomes a transparent solution, thus obtaining the sulfur source solution with a concentration of 0.1mol / L.
[0026] S2. Under inert gas protection, 8 mL of OLA was evacuated three times, then heated to 120°C and evacuated for 60 min to remove moisture and oxygen. The temperature was then raised to 300°C, and a mixture of 0.8 mL of tri-n-octylphosphine and 0.5 mL of 1 mol / L selenium source solution was rapidly injected. After the temperature stabilized, a mixture of 0.8 mL of tri-n-octylphosphine, 0.475 mL of 1 mol / L diethylzinc solution, and 0.25 mL of 0.1 mol / L gallium precursor solution was injected. The mixture was held at 300°C for 10 min to generate ZnSe:Ga quantum dot nuclei.
[0027] S3. Then, the mixed solution, consisting of 5.5 mL octadecene, 5.5 mL tri-n-octylphosphine, 3 mL 1 mol / L selenium source solution, 2.85 mL diethylzinc solution, and 1.5 mL 0.1 mol / L gallium precursor solution, was added dropwise at a rate of 2 mL / h. The fluorescence peak position was monitored in real time, and the addition was stopped when the peak position reached 450 nm. The solution was then cooled to room temperature to obtain ZnSe:Ga quantum dots.
[0028] S4. After the reaction is complete, lower the temperature to 110℃ and inject hydrofluoric acid solution into the reaction system to clean the surface of the nanocrystal nuclei. S5. Add 5 mL of the ZnSe:Ga quantum dot solution prepared in S3 to the reaction flask. At 300 °C, add a mixture of 1 mL of zinc oleate solution, 0.7 mL of 0.1 mol / L selenium source solution, and 0.3 mL of 0.1 mol / L sulfur source solution dropwise at a rate of 1 mL / h to grow a ZnSeS transition shell. Subsequently, add a mixture of 1 mL of zinc oleate solution and 17 μL of octyl mercaptan dropwise at a rate of 1 mL / h to grow a ZnS outer shell. After the reaction is complete, cool to room temperature and add ethanol as an antisolvent to precipitate the quantum dots, obtaining ZnSe:Ga / ZnSeS / ZnS core-shell structured quantum dots.
[0029] Example 2 The only difference between this embodiment and Embodiment 1 is that the amount of gallium precursor has been adjusted. The specific preparation method includes the following steps: S1, Same as Example 1.
[0030] S2. Add 8 mL of oleylamine to the reaction flask, evacuate the flask three times under inert gas protection, heat to 120°C, and evacuate for 60 minutes. Raise the temperature to 300°C, and inject a mixture of 0.8 mL of tri-n-octylphosphine and 0.5 mL of 1 mol / L selenium source solution. Then inject a mixture of 0.8 mL of tri-n-octylphosphine, 0.45 mL of 1 mol / L diethylzinc solution, and 0.5 mL of 0.1 mol / L gallium precursor solution, and maintain the temperature at 300°C for 10 minutes.
[0031] S3. A mixed solution consisting of 5.5 mL of 1-octadecene, 5.5 mL of tri-n-octylphosphine, 3 mL of 1 mol / L selenium source solution, 2.70 mL of diethylzinc, and 3 mL of 0.1 mol / L gallium precursor solution was added dropwise at a rate of 2 mL / h. The fluorescence peak position was monitored in real time, and the addition was stopped when the peak position reached 450 nm. The solution was then cooled to room temperature to obtain ZnSe:Ga quantum dots.
[0032] S4, Same as Example 1.
[0033] S5, same as Example 1.
[0034] Comparative Example 1 The only difference between this comparative example and Example 1 is that no gallium precursor solution was added in this comparative example; all other conditions are the same.
[0035] The ZnSe:Ga quantum dots prepared in Examples 1-2 and the ZnSe quantum dots prepared in Comparative Example 1 were dispersed in n-hexane, and UV-Vis absorption spectroscopy, fluorescence spectroscopy, and photoluminescence spectroscopy were performed. The UV-Vis absorption spectroscopy results are as follows: Figure 1 As shown in (a) above, the fluorescence spectroscopy test results are as follows: Figure 1As shown in (b) above, the photoluminescence growth spectrum test results are as follows: Figure 1 As shown in (c), the transmission electron microscope image of the ZnSe:Ga quantum dots prepared in Example 2 is as follows. Figure 1 As shown in (d) in the figure.
[0036] Depend on Figure 1 As shown in (a), with the increase of Ga doping, the first exciton absorption peak in the absorption spectrum undergoes a slight red shift, indicating that doping leads to a slight narrowing of the band gap. 3+ Ion substitution of Zn 2+ Excess electrons are introduced at the site, affecting band edge absorption through the Burstein-Moss effect or impurity energy levels, but the overall band gap does not change much, and the blue light emission characteristics are still maintained.
[0037] Depend on Figure 1 As shown in (b), the emission peak of undoped ZnSe is approximately 430 nm (with a purplish-blue tint); after doping with 5% Ga, the emission peak redshifts to approximately 450 nm; after doping with 10% Ga, the emission peak further redshifts to approximately 460 nm, and the peak width does not broaden significantly. Ga doping effectively modulates the emission wavelength of ZnSe, causing it to move from the purplish-blue region to the pure blue light region (450-460 nm), and defect luminescence is suppressed after doping, indicating that Ga plays a role in passivating surface states or regulating energy levels.
[0038] Depend on Figure 1 As shown in (c), with the continuous addition of the precursor, the quantum dot size increases, and the fluorescence peak position continuously redshifts from 406 nm to 471 nm. By controlling the secondary growth time or the amount of precursor, tunable emission covering near-ultraviolet to pure blue light can be achieved, demonstrating the flexibility of this method in size / wavelength control.
[0039] Depend on Figure 1 As shown in (d), the quantum dots are approximately spherical, uniformly dispersed, and have an average size of about 9 nm. They maintain good monodispersity and morphological regularity even with high doping levels, providing a high-quality core for subsequent shell growth and device applications.
[0040] Figure 2 The image shows the XRD pattern of the ZnSe:Ga / ZnSeS / ZnS core-shell quantum dots prepared in Example 2. Figure 2 It can be seen that the diffraction peaks are consistent with the standard card of cubic zincblende ZnSe, and no Ga-related impurity peaks are found; the peak positions of the core-shell structure are slightly shifted to a large angle, and the prepared ZnSe, ZnSe:Ga, ZnSe:Ga / ZnSeS / ZnS are all cubic crystal systems.
[0041] Figure 3 Transmission electron microscopy (TEM) images of the samples prepared in Examples 1-2 and Comparative Example 1, by... Figure 3It can be seen that the sample diameter of Comparative Example 1 is approximately 4.98 nm, the sample diameter of Example 1 is approximately 7.17 nm, and the sample diameter of Example 2 is approximately 7.53 nm. The increase from 4.98 nm to 7.17 nm is mainly due to the secondary growth process (size increase), and not just due to doping. The shell growth increased the diameter by approximately 0.36 nm, corresponding to a shell thickness of approximately 0.18 nm, proving the successful coating of a thin ZnSeS / ZnS layer. Furthermore, the samples are all well dispersed and show no agglomeration.
[0042] Application examples The ZnSe:Ga / ZnSeS / ZnS core-shell quantum dots prepared in Example 2 were used to prepare light-emitting diode devices. Patterned ITO conductive glass was used as the anode. After cleaning and ultraviolet ozone treatment, hole injection layer, hole transport layer, quantum dot light-emitting layer, electron transport layer and metal cathode were prepared in sequence.
[0043] The hole injection layer is formed using PEDOT through spin coating and annealing; the hole transport layer is formed using PF8Cz solution spin coating; subsequently, the blue quantum dot dispersion prepared in this invention is spin-coated onto the surface of the hole transport layer to form a quantum dot light-emitting layer; then, a ZnMgO nanocrystal solution is spin-coated as an electron transport layer. Finally, an Al electrode is deposited by vacuum thermal evaporation to obtain a blue quantum dot light-emitting diode device.
[0044] The performance of the prepared blue quantum dot light-emitting diode device was tested, and the test results are as follows: Figure 4 and Figure 5 As shown.
[0045] Depend on Figure 4 It can be seen that the maximum EQE of this blue quantum dot light-emitting diode device reaches 14.36%, and it remains effective over a wide current density range (approximately 1-100 mA / cm²). 2 The quantum dot maintains an EQE of over 10% with a small roll-off. The high EQE is attributed to the high quantum yield (>85%) of the quantum dot itself and reasonable device energy level matching. The low roll-off indicates good carrier injection balance and less defect-assisted recombination.
[0046] Depend on Figure 5 As can be seen from the curve trend, the brightness of the device decreases exponentially with the extension of working time. This is a common degradation behavior in organic / quantum dot light-emitting diodes, mainly attributed to the aging of the light-emitting layer material, charge accumulation, and the gradual generation of interface defects.
[0047] Therefore, this invention employs the aforementioned high-quality gallium-containing nanocrystals that emit pure blue light and their preparation method. By introducing Ga doping into ZnSe quantum dots, ZnSe:Ga quantum dots are prepared, achieving pure blue light emission from the ZnSe system, with the emission peak position adjustable to between 450-460 nm. Furthermore, by epitaxially growing a shell layer, surface defects and interfacial nonradiative recombination are effectively suppressed, significantly improving the stability and optical performance of the quantum dots. The constructed ZnSe:Ga / ZnSeS / ZnS core-shell structure quantum dots exhibit high luminous efficiency. Combined with additional ligands to further passivate surface defects, their quantum yield can reach over 85%, laying a solid foundation for realizing high-performance blue QLED emitting layer materials.
[0048] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for preparing high-quality gallium-containing nanocrystals that emit pure blue light, characterized in that: Includes the following steps: S1. Prepare zinc precursor solution, gallium precursor solution and group VI precursor solution, wherein the element in group VI precursor solution is one or both of selenium and sulfur; S2. Under a protective atmosphere, the organic amine solvent is heated, and a Group VI precursor solution is added, followed by a zinc precursor solution and a gallium precursor solution. The reaction generates gallium-doped nanocrystal nuclei. Then, the Group VI precursor solution, zinc precursor solution, and gallium precursor solution are added dropwise to obtain gallium-doped quantum dots. S3. After the reaction is complete, lower the temperature and inject hydrofluoric acid solution into the reaction system to clean the surface of the nanocrystal nuclei. S4. After cleaning, the reaction system is heated and a mixed solution of zinc precursor solution and group VI precursor solution is added to grow a transition shell layer epitaxially on the surface of the nanocrystal nucleus. Finally, a mixed solution of zinc precursor solution and organic alcohol is added to grow the outer shell layer. S5. After the outer shell layer growth is completed, the temperature is lowered to room temperature, and an antisolvent is added to precipitate high-quality gallium-containing nanocrystals that emit pure blue light.
2. The method for preparing high-quality gallium-containing nanocrystals emitting pure blue light according to claim 1, characterized in that: In S1, the zinc precursor solution is one or more of diethylzinc solution and zinc oleate solution; the zinc oleate solution is prepared by dissolving zinc acetate in a mixed solvent of oleylamine, oleic acid and octadecene, wherein the volume ratio of oleylamine, oleic acid and octadecene is 1:1:8 and the dissolution temperature is 80-120℃.
3. The method for preparing high-quality gallium-containing nanocrystals emitting pure blue light according to claim 1, characterized in that: In S1, the gallium precursor solution is prepared by dissolving gallium chloride in a mixed solvent of oleylamine and octadecene. The concentration of the prepared gallium precursor solution is 0.1 mol / L, the volume ratio of oleylamine to octadecene is 1:9, and the dissolution temperature is 80-120℃.
4. The method for preparing high-quality gallium-containing nanocrystals emitting pure blue light according to claim 1, characterized in that: In S1, the preparation of the Group VI precursor solution is as follows: the elemental substance of Group VI is dissolved in tri-n-octylphosphine to obtain the Group VI precursor solution, and Group VI precursor solutions with concentrations of 1 mol / L and 0.1 mol / L are prepared respectively.
5. The method for preparing high-quality gallium-containing nanocrystals emitting pure blue light according to claim 1, characterized in that: In S2, the organic amine solution is heated to 100-120℃, evacuated for 30-60 min, and then heated to 300℃. The organic amine is a chain primary amine, which is one of oleylamine or octadecylamine. The concentration of the Group VI precursor solution is 1 mol / L, and the dropping rate of the Group VI precursor solution, zinc precursor solution, and gallium precursor solution is 1-2 mL / h.
6. The method for preparing high-quality gallium-containing nanocrystals emitting pure blue light according to claim 1, characterized in that: In S3, the temperature drops to 110℃.
7. The method for preparing high-quality gallium-containing nanocrystals emitting pure blue light according to claim 1, characterized in that: In S4, when the temperature is raised to 300℃, the concentration of the Group VI precursor solution during the growth of the transition shell is 0.1 mol / L, the organic alcohol is a chain thiol, and the chain thiol is octylthiol.
8. The method for preparing high-quality gallium-containing nanocrystals emitting pure blue light according to claim 1, characterized in that: In S4, the nanocrystalline nucleus is one of ZnSe, ZnS, or ZnSeS.
9. The method for preparing high-quality gallium-containing nanocrystals emitting pure blue light according to claim 1, characterized in that: In S5, the antisolvent is one or more of acetone, methanol, and ethanol.
10. A high-quality gallium-containing nanocrystal that emits pure blue light, characterized in that: It was prepared using the method described in any one of claims 1-9 for preparing high-quality gallium-containing nanocrystals that emit pure blue light.
